Impact of Local Anesthesia Techniques on Epididymal Morphology: An Experimental Study - Kodirov M.D. (American Journal of Bioscience and Clinical Integrity, 2026)
This experimental study evaluated morphological changes in epididymal tissue following different methods of local anesthesia using lidocaine and novocaine. The effects of intratesticular injection and conduction anesthesia on epididymal tubules, stromal structures, and microvasculature were assessed using histological (hematoxylin–eosin, van Gieson) and morphometric analyses. Intratesticular administration resulted in significantly more pronounced structural damage compared to conduction anesthesia, including epithelial disruption, thickening of intertubular septa, and microcirculatory disturbances (p < 0.05). The most severe alterations were observed after intratesticular novocaine injection, whereas conduction anesthesia with lidocaine showed minimal morphological changes. The integrated structural injury index (ISI′) confirmed a significant relationship between the method of administration and tissue damage severity. These findings indicate that the anesthesia technique is a key determinant of epididymal tissue response and support the use of less traumatic approaches, particularly in patients of reproductive age.